(untitled) (Journal of the College of Basic Education, 2022)
This research aims to know the degree of possession of geography teachers in the preparatory stage for the competencies of e-learning via the Internet from their point of view, and within the framework of the objectives that the research seeks to achieve, the research was limited to teachers of geography for the academic year (2016-2017 AD) for the preparatory stage. The research sample was formed From (86) male and female teachers, and they are (45) teachers, and (41) female teachers, who are teachers of geography in the preparatory stage affiliated with government schools in the Directorate of Dhi Qar Education Department of Al-Rifai Education, and to achieve the objectives of the research, the researchers adopted a questionnaire that included (50) adequacy They were divided into five domains, which are competencies (using a computer, using the Internet and its tools, e-learning culture,